2013
DOI: 10.1021/jp402977y
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll Triplet Quenching and Photoprotection in the Higher Plant Monomeric Antenna Protein Lhcb5

Abstract: In oxygenic photosynthetic organisms, chlorophyll triplets are harmful excited states readily reacting with molecular oxygen to yield the reactive oxygen species (ROS) singlet oxygen. Carotenoids have a photoprotective role in photosynthetic membranes by preventing photoxidative damage through quenching of chlorophyll singlets and triplets. In this work we used mutation analysis to investigate the architecture of chlorophyll triplet quenching sites within Lhcb5, a monomeric antenna protein of Photosystem II. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 58 publications
2
43
0
2
Order By: Relevance
“…It could be asked whether the lower yield of 1 O 2 derives from the lower level of 1 Chl* excited states and, thus, from an increased probability of 3 Chl* formation. We observed that the decrease of 1 O 2 formation in LHCBM9, as compared with LHCBM2/3, is stronger than the decrease of fluorescence yield, suggesting that additional mechanisms are also involved such as improved 3 Chl* quenching and/or 1 O 2 scavenging by bound carotenoids (Ballottari et al, 2013). Second, in sulfur deficiency, PSII supercomplexes containing LHCBM9 are found in a more dissipative state compared with PSII supercomplexes purified from kd-L9.1/2, thus decreasing overexcitation of PSII reaction centers and photoinhibition (Figure 4, Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…It could be asked whether the lower yield of 1 O 2 derives from the lower level of 1 Chl* excited states and, thus, from an increased probability of 3 Chl* formation. We observed that the decrease of 1 O 2 formation in LHCBM9, as compared with LHCBM2/3, is stronger than the decrease of fluorescence yield, suggesting that additional mechanisms are also involved such as improved 3 Chl* quenching and/or 1 O 2 scavenging by bound carotenoids (Ballottari et al, 2013). Second, in sulfur deficiency, PSII supercomplexes containing LHCBM9 are found in a more dissipative state compared with PSII supercomplexes purified from kd-L9.1/2, thus decreasing overexcitation of PSII reaction centers and photoinhibition (Figure 4, Table 1).…”
Section: Discussionmentioning
confidence: 81%
“…Although lhcsr KO exhibited prompt recovery in the dark, npq4 did not, implying photoinhibition ( Figure 4A). In order to discriminate between genuine qE and slower inhibitory components, namely, qZ or qI (Dall'Osto et al, 2005;Kalituho et al, 2007;Ballottari et al, 2013), we isolated the rapid qE component of NPQ by freezing samples at different times up to 6 min under HL and following further incubation in dark for up to 5 min to allow for selective relaxation of only qE (Figures 5E and 5F; Supplemental Figure 6). Dark-recovered (5 min) minus light-only (6 min) difference spectra, depicted in Figure 6A, show that whereas lhcsr KO chloroplasts underwent quenching of only the PSII component, both psbs KO and wild-type chloroplasts quenched both PSI and PSII emissions.…”
Section: Npq Dissection Of Psii Versus Psi By 77k Fluorescence Spectrmentioning
confidence: 99%
“…Excess photons increase the amount of singlet chlorophyll ( 1 Chl*) and, thus, the probability for formation of triplet chlorophyll ( 3 Chl*) and singlet oxygen ( 1 O 2 ), with consequent photoinhibition that limits growth. Oxygenic organisms have evolved different photoprotective mechanisms in order to avoid the formation of reactive oxygen species, including triplet quenching (Dall'Osto et al, 2012;Ballottari et al, 2013), reactive oxygen species scavenging (Baroli et al, 2003;Dall'Osto et al, 2010), and alternative electron transport pathways (Cardol et al, 2011). In addition to these constitutive mechanisms, a rapidly inducible process known as nonphotochemical quenching (NPQ) is activated within seconds upon exposure to excess light and then catalyzes thermal dissipation within the photosystem II (PSII) antenna system (Niyogi and Truong, 2013;de Bianchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Singlet excited Chl * can decay into triplets (3 Chl * ) which sensitize molecular oxygen to form singlet oxygen, which induces damage in its local environment by destroying lipids and nucleic acids and proteins. [1], [2], [3] Cars are able to accept the triplets from chlorophylls (chls) by triplet energy transfer (TET), and dissipate the excess energy to heat. [4] The efficiency of Chl triplet quenching is 95% in antenna complexes of Photosystem II in higher plants, and the timescale of TET from Chls to Cars has been found to be faster than 500 ps in the major light-harvesting complex of Photosystem II (LHCII).…”
mentioning
confidence: 99%